The push factors of young entrepreneur in handicrafts industry: a case study at Kampar, Perak / Siti Azwan Ameen - Ameen, Siti Azwan (2011)
Entrepreneurs are people who take risks to enter the world of careers as businessmen/businesswomen. Year by year the number of entrepreneurs is increasing and they had been helping with the Malaysian economy. As an entrepreneur, one must take risks in terms of money and time taken to ensure the success of the business. Profits they earn can help improve the economy and local living standards. It also helps the unemployed to get a permanent job. The case study is set on the rural entrepreneurs to increase their standard of living by producing hand-made crafts. They not only maintain the cultural characteristics of their results but they also improvise the products produced to be in line with current trends. Being an entrepreneur is not easy having to face many obstacles to be successful. Government support is also needed to help new entrepreneurs to participate. The Development and Distribution of Entrepreneurs Sectors in State Economic Planning Unit helps the entrepreneurs in the state to promote their products either locally or internationally. There are other companies and institutions that help the entrepreneurs to develop such as MARA, INSKEN and also PEDSC. given support from government. However, they must grab this chance as an opportunity.